Anti-Candidal Activity and Functional Mapping of Recombinant and Synthetic Neosartorya fischeri Antifungal Protein 2 (NFAP2) - Tóth, Liliána; Váradi, Györgyi; Borics, Attila; Batta, Gyula; Kele, Zoltán; Vendrinszky, Ákos; Tóth, Roberta; Ficze, Hargita; Tóth, Gábor K.; Vágvölgyi, Csaba; Marx, Florentine; Galgóczy, László (Frontiers in Microbiology, 2018)
The increasing number of life-threatening Candida infections caused by antifungal drug-resistant strains urges the development of new therapeutic strategies. The small, cysteine-rich, and cationic Neosartorya fischeri antifungal protein 2 (NFAP2) effectively inhibits the growth of Candida spp. Limiting factors of its future application, are the low-yield production by the native producer, unavailable information about potential clinical application, and the unsolved relationship between the structure and function. In the present study we adopted a Penicillium chrysogenum-based expression system for bulk production of recombinant NFAP2. Furthermore, solid-phase peptide synthesis and native chemical ligation were applied to produce synthetic NFAP2. The average yield of recombinant and synthetic NFAP2 was 40- and 16-times higher than in the native producer, respectively. Both proteins were correctly processed, folded, and proved to be heat-stable. They showed the same minimal inhibitory concentrations as the native NFAP2 against clinically relevant Candida spp. Minimal inhibitory concentrations were higher in RPMI 1640 mimicking the human inner fluid than in a low ionic strength medium. The recombinant NFAP2 interacted synergistically with fluconazole, the first-line Candida therapeutic agent and significantly decreased its effective in vitro concentrations in RPMI 1640. Functional mapping with synthetic peptide fragments of NFAP2 revealed that not the evolutionary conserved antimicrobial γ-core motif, but the mid-N-terminal part of the protein influences the antifungal activity that does not depend on the primary structure of this region. Preliminary nucleic magnetic resonance measurements signed that the produced recombinant NFAP2 is suitable for further structural investigations.